Fatal meningococcal meningitis in a HIV-infected patient caused by serogroup C Neisseria meningitidis belonging to the non-hypervirulent clonal complex ST-60 (cc60) - Andrade,Claudia Ferreira de (2011)
Meningococcal strains belonging to clonal complex cc60 are not associated with hypervirulent lineages and were never reported as causing disease in Latin American countries. This is the first report of a fatal meningitis case caused by a cc60 clonal complex meningococcus in Brazil. Despite the immune-compromised state of the patient, the fatal outcome here described shows the potential pathogenic behavior of strains belonging to this clonal complex and how compromised hosts can be susceptible to meningococcal infections even if the strain is not particularly invasive.